Sex-dependent actions of amyloid beta peptides on hippocampal choline carriers of postnatal rats - Kristofiková, Z; Rícný, J; Kozmiková, I; Rípová, D; Zach, P; Klaschka, J (Neurochemical research, 2006)
It is suggested that amyloid beta peptides (Abeta) play a role in the pathogenesis of Alzheimer disease but their physiological function is still unknown. However, low pM-nM concentrations mediate a hypofunction of a basal forebrain cholinergic system without marked signs of neurotoxicity. In this study, we compared in vitro effects of soluble nonaggregated human Abeta 1-40 and 1-42 either on synaptosomal hemicholinium-3 sensitive choline carriers or on membrane fluidity in hippocampi of male and female Wistar rats aged 7 and 14 days or 2-3 months. The results indicate age- and sex-dependent effects mediated by peptides at nM concentrations but no significant differences between both fragments. Namely, opposite actions were observed in 14-day (the increase in the choline uptake and membrane fluidity) when compared to 7-day old and adult males (the mild drops). Lineweaver-Burk plot analysis revealed that the enhancement of the high-affinity choline transport in 14-day old males occurs via alterations in K (M )and the change was accompanied by a mild increase in the specific binding of [3H]hemicholinium-3. On the other hand, no age-dependent differences were found in females. Rat Abeta 1-40 mediated similar effects on 14-day old rats as the corresponding human fragment. Moreover, higher levels of soluble peptides were detected in immature when compared to mature male brains by means of competitive ELISA. Our study indicates that Abeta could play a role in postnatal sexual differentiation of hippocampal cholinergic system.
Keywords: fluidita membrány; membránové transportní proteiny; Sex Factors; techniky in vitro; Humans; Fluorescence Polarization; Choline; Female; ELISA; věkové faktory; krysa rodu Rattus; Hippocampus; radioligandová zkouška; lidé; Membrane Transport Proteins; zvířata; amyloidní beta-protein; cholin; hipokampus; difenylhexatrien; Enzyme-Linked Immunosorbent Assay; potkani Wistar; sexuální faktory; synaptozomy; Synaptosomes; Peptide Fragments; fluorescenční barviva; ženské pohlaví; Fluorescent Dyes; Amyloid beta-Peptides; fluorescenční polarizace; Male; Rats, Wistar; Radioligand Assay; Membrane Fluidity; peptidové fragmenty; In Vitro Techniques; Rats; Diphenylhexatriene; Age Factors; Animals; mužské pohlaví